Cohesivity Fisheries Community in the Face of Climate Change on the Coast of Western Java - Adriana, Galuh; K. Pandjaitan, Nurmala; Hadi Dharmawan, Arya (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABTRACTThe conditions of fishermen is very dependent with nature. Climate change that happening makes nature more difficult to predict. That can make the living of fishermen more vulnerabel. Communities that have a strong cohesiveness will have a collective action to deal with climate change. The purpose of this study is to see the level of cohesiveness fisherman in the face of climate change. The method used is mix method using questionnaire, observation and in-depth interviews. The number of respondents was 100 people. The selection of respondents was done by simple random sampling technique, where the study population are members of “raskin” program from government. The results are fisheries community have a strong social capital, sense of community and community collective efficacy, which is produced strong cohesiveness. However, in reality what is perceived is not necessarily reflected in everyday life. Collective action found only in activities that support public facilities. However, collective action for the economic interests only occurs in certain interest groups. According the results can be argued that the level of fishing community cohesiveness is high, but only produce preparadness for climate change.Keywords: social cohesion, collective action, fisheries communityABSTRAKKehidupan nelayan sangat bergantung dengan alam. Perubahan iklim yang terjadi membuat alam semakin sulit untuk diprediksi. Kondisi tersebut membuat kehidupan nelayan semakin vulnerabel. Komunitas yang memiliki kohesivitas yang kuat akan memiliki aksi kolektif untuk menghadapi perubahan iklim. Penelitian ini bertujuan untuk melihat derajat kohesivitas komuitas nelayan dalam mengahadapi perubahan iklim. Metode yang digunakan adalah mix method dengan menggunakan kuesioner, observasi dan wawancara mendalam. Jumlah responden adalah 100 orang. Pemilihan responden dilakukan dengan teknik simple random sampling, dimana populasi penelitian adalah anggota komunitas penerima program beras raskin dari pemerintah. Hasil penelitian adalah komunitas nelayan memiliki modal sosial, sense of community dan community collective efficacy yang kuat, yang akan menghasilkan kohesivitas yang kuat. Akan tetapi, apa yang dirasakan belum tentu tercerimin pada kehidupan sehari-hari. Aksi kolektif hanya terdapat pada kegiatan yang mendukung fasilitas umum. Akan tetapi aksi kolektif untuk kepentingan ekonomi hanya terjadi pada kelompok-kelompok kepentingan tertentu. Berdasarkan hasil dapat dikatakan bahwa tingkat kohesivitas komunitas nelayan tinggi, tetapi hanya menghasilkan kesiapan untuk menghadapi perubahan iklim.Kata kunci: kohesivitas, aksi kolektif, komunitas pesisir